2019
DOI: 10.1017/s0025315419000778
|View full text |Cite
|
Sign up to set email alerts
|

Barnacle cover modifies foraging behaviour of the intertidal limpetPatella vulgata

Abstract: Limpets and barnacles are important components of intertidal assemblages worldwide. This study examines the effects of barnacles on the foraging behaviour of the limpet Patella vulgata, which is the main algal grazer in the North-west Atlantic. The behaviour of limpets on a vertical seawall on the Isle of Man (UK) was investigated using autonomous radio-telemetry, comparing their activity patterns on plots characterized by dense barnacle cover and plots from which the barnacles had been removed. Limpet behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The importance of grazing interactions in limiting the lower limit of kelp in the shallow subtidal zone was shown on the ruined breakwater in Port Erin, Isle Of Man (Jones & Kain, 1967). Interactions between barnacles and limpets (Hawkins & Hartnoll, 1982 b ; Santini et al ., 2019) and settlement patterns of barnacles in relation to wind patterns (Hawkins & Hartnoll, 1982 a ) were all investigated on the same Raglan Pier in Port Erin. The simplicity of replicated artificial shore parallel breakwaters at Elmer in Sussex, UK, enabled the respective roles of grazing by limpets in preventing establishment of fucoid algae and wave action reducing persistence of older plants to be disentangled by a combination of field experiments and modelling (Jonsson et al ., 2006).…”
Section: Overview and Synthesismentioning
confidence: 99%
“…The importance of grazing interactions in limiting the lower limit of kelp in the shallow subtidal zone was shown on the ruined breakwater in Port Erin, Isle Of Man (Jones & Kain, 1967). Interactions between barnacles and limpets (Hawkins & Hartnoll, 1982 b ; Santini et al ., 2019) and settlement patterns of barnacles in relation to wind patterns (Hawkins & Hartnoll, 1982 a ) were all investigated on the same Raglan Pier in Port Erin. The simplicity of replicated artificial shore parallel breakwaters at Elmer in Sussex, UK, enabled the respective roles of grazing by limpets in preventing establishment of fucoid algae and wave action reducing persistence of older plants to be disentangled by a combination of field experiments and modelling (Jonsson et al ., 2006).…”
Section: Overview and Synthesismentioning
confidence: 99%
“…Our results show that the barnacle B. glandula has negative effects on S. granularis but positive effects on littorinids. There are many other examples of negative barnacle-limpet interactions (Dayton, 1971;Branch, 1976;Hawkins, 1983;Dungan, 1986;Santini et al, 2019;Ellrich et al, 2020), but in New South Wales, Creese (1982) showed that a small species of limpet, Patelloida latistrigata, benefits from the presence of barnacles that provide a refuge from competition with a larger species of limpet, Cellana tramoserica, which is excluded because it cannot move over and feed effectively on barnacles. Again, size matters.…”
Section: Barnacles Limpets and Periwinklesmentioning
confidence: 99%
“…Limpets [genus Patella (Gastropoda: Patellidae)] are edible marine molluscs found in high amounts in the northern European and Mediterranean coasts. Patella vulgata is one of the main limpet species (along with Patella ulyssiponensis) found on the Irish coast. Marine organisms such as molluscs are consumed in many countries as part of the daily diet and are rich in protein and nitrogenous components. These marine-derived proteins have a balanced amino acid (AA) profile with a high content of essential AAs (EAAs) along with high digestibility. Determination of the protein digestibility-corrected AA score (PDCAAS) has been employed for the evaluation of protein quality; however, to date, only a limited number of reports exist on the protein digestibility of molluscs, , and, to our knowledge, no data on limpet protein has yet been reported.…”
Section: Introductionmentioning
confidence: 99%